Spatial distribution and characterization of Chagas disease cases in the State of Maranhão, Brazil from 2008 to 2018 (Research, Society and Development, 2020)
This study refers to a retrospective and descriptive epidemiological study of a population nature, using secondary data from cases of patients with ACD from 2008 to 2018 (n = 59) in the state of Maranhão - Brazil. This data is complete in the Notification Disease Information System (SINAN). The information was made available on the website of the Department of Informatics of the Unified Health System (DATASUS). The cartographic data, ie the digital map with the mesh of the municipalities of MA, were obtained by the Brazilian Institute of Geography and Statistics (IBGE) in a file compatible with Terra View software 4.2.2. Between 2008 and 2018, according to SINAN, in Maranhão, there were a total of 59 confirmed cases of ACD, with higher prevalence in males, aged between 20 and 39 years, oral contamination is the main form of Transmission 89.8 of the cases evolved to cure and 91.5% of the cases were confirmed by laboratory examination. Disease distribution occurred heterogeneously, possibly due to the demographic dynamics of the municipality. Moreover, Chagas disease remains an important health problem in the state of Maranhão and local aspects influence the monthly distribution of confirmed cases, also presented age range affected and the treatment employed by the government is satisfactory. Different relationships between the variables studied and the occurrence of the disease were observed, many corroborating the literature data.